A 0.65-V 12-16-GHz Sub-Sampling PLL With 56.4-fsrms Integrated Jitter and −256.4-dB FoM - Zhang, Zhao; Zhu, Guang; Patrick Yue, C. (IEEE journal of solid-state circuits, 2020)
This article presents a low-voltage (LV) sub-sampling phase-locked loop (LVSSPLL). The architecture of hybrid dual-path loop-based SSPLL is proposed to mitigate the issue of limited output voltage range of LV charge pump (CP). Four LV building blocks, including a proportional path sub-sampling CP (SSCP), an integral path SSCP, an LV sub-sampling phase detector, and an LV digitally controlled capacitor array in the LC -based voltage-controlled oscillator, are proposed to simultaneously reduce the PLL integrated jitter and the jitter variation over supply voltage variation. Fabricated in 40-nm CMOS process with a core active area of 0.24 mm 2 , the LVSSPLL operates at 0.65-V supply and achieves 12-16-GHz tuning range, 56.4-fs integrated jitter at 14 GHz, 7.2-mW power consumption, and −256.4-dB figure-of-merit (FoM). The measured integrated jitter variation is less than 14.5 fs within the supply voltage range from 0.62 to 0.7 V, which shows robustness over supply voltage variation.